2021
DOI: 10.1186/s41077-021-00166-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to explore Safety-I and Safety-II perspectives in in situ simulations—the structured what if functional resonance analysis methodology

Abstract: Objectives With ever increasingly complex healthcare settings, technology enhanced simulation (TES) is well positioned to explore all perspectives to enhance patient safety and patient outcomes. Analysis from a Safety-II stance requires identification of human adjustments in daily work that are key to maintaining safety. The aim of this paper is to describe an approach to explore the consequences of human variability from a Safety-II perspective and describe the added value of this to TES. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…This definition of safety has been used in other simulation studies. [23][24][25] We selected specific criteria such as wait time, patients leaving without being seen or accident reports, which are based on literature on safety metrics in EM. 26 27 We explored two safety concepts: 'ongoing' safety of patients being managed while ISS was ongoing in the ED (measured by ISS cancellation rate, accident reports, ED median wait time, number of patients who left without being seen) and 'future patient' safety with more long-term benefits from ISS (measured by LST evaluation).…”
Section: Discussionmentioning
confidence: 99%
“…This definition of safety has been used in other simulation studies. [23][24][25] We selected specific criteria such as wait time, patients leaving without being seen or accident reports, which are based on literature on safety metrics in EM. 26 27 We explored two safety concepts: 'ongoing' safety of patients being managed while ISS was ongoing in the ED (measured by ISS cancellation rate, accident reports, ED median wait time, number of patients who left without being seen) and 'future patient' safety with more long-term benefits from ISS (measured by LST evaluation).…”
Section: Discussionmentioning
confidence: 99%
“…However, it must also be considered that drivers are usually not well trained, and such a complex function allocation could lead to confusion besides advantages. Therefore, in future research, the FRAM model for the overtaking scenario and the current design recommendations should be checked by "what-if analyses" [99,100] as various instantiations of the FRAM model in other scenarios (for example in curves or bad weather conditions) on the one hand, and on the other hand for dynamic performance changes over time, such as by Hirose et al [57]. Furthermore, it is not only the performance variability that can change but also new functions will emerge through the collaboration between humans and automation, which is why an adaptation of the FRAM model in relation to the context conditions is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Newer methods such as the Systems Theoretic Accident Model and Process (STAMP), AcciMAP and Functional Resonance Analysis Methodology (FRAM) look at interdependencies and interactions between components of the system. These methods are dynamic, observing how individuals might act under different circumstances and how different levels of the system such as regulatory bodies and management as well as production pressures might change the circumstances [23]. Patterns may be found that will inform future clinicians and managers as to how best adapt to the system or re‐engineer it, rather than finding a simple, convenient but ultimately unhelpful root cause.…”
Section: Moving Beyond Error As a Causementioning
confidence: 99%